Life Table of Mushroom Fly, Bradysia ocellaris - Rostaman, Rostaman (Metamorfosa: Journal of Biological Sciences, 2023)
Mushroom fly, Bradysia ocellaris  Comstock, is a new pest species on oyster mushroom  cultivation in Bandung and other districts in West Java. Based on information, the insect widely distributes over countries.The aim of this research was to investigate life table parameters of the insect.Insects were reared in the laboratory using oyster mushroom media as their foods. The result showed that intrinsic rate of population growth () was 0.157, net reproductive rate () 23 individu/generation, and  mean generation time ( T ) 20,5 days. This informartion is important in reproductivity of insect pest in three weeks.